Is there a Unique or non Unique Value Profile for Albanian Social Actors? (The Study Case of Tirana Electorate in 2003, 2008, 2010 and 2011) - Kocani, Aleksandër (Richtmann Publishing, 2013)
This paper shows the results of an empirique panel study carried out in 2003, 2008, 2010 and 2010. The start point for thispaper was the notice of C.Brooks and J.Manza about the possibility for reaching opposite results if you repeat the Inglehart’sinterviews by other methods. Here one may ask: Is there a indicator of the problem related with the value’s profile nature ofsocial actors. In this case, you may consider two alternatives: 1) the social actor has only one value profile, or on the contrary2) he does not has such a value profile. The last one may be separated into two cases: a) or there is not a value profile, but itis created by interaction between knowledge subject and object ; or b) there are two opposite value profile which are selectedoccasionally. The empirical testing is possible if one may find or not the influence upon the respondents during the intreviews.If there is only one value profile you can not find possible influencies. On the contrary you have to consider there is not onevalue profile.